2011
DOI: 10.1124/jpet.111.185728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repeated 3,4-Methylenedioxymethamphetamine Administration on Neurotransmitter Efflux and Sensory-Evoked Discharge in the Ventral Posterior Medial Thalamus

Abstract: 3,4-Methylenedioxymethamphetamine (MDMA) is known to enhance tactile sensory perception, an effect that contributes to its popularity as a recreational drug. The neurophysiological basis for the effects of MDMA on somatosensation are unknown. However, MDMA interactions with the serotonin transporter (SERT) and subsequent enhancement of serotonin neurotransmission are well known. The rat trigeminal somatosensory system receives serotonergic afferents from the dorsal raphe nucleus. Because these fibers express S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…; Starr et al . ). It is well known that behavioral responses can be altered in complex ways because of the interaction between serotonergic and catecholaminergic systems.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Starr et al . ). It is well known that behavioral responses can be altered in complex ways because of the interaction between serotonergic and catecholaminergic systems.…”
Section: Discussionmentioning
confidence: 97%
“…In support of this concept, 'binge' dosing (three or more doses in one session) was often used to elicit a long lasting increase in extracellular brain 5HT for achieving a recreational or neurological response (Baumann et al 2008b). In addition to 5HT, MDMA also causes excessive increases in extracellular dopamine and noradrenalin (Baumann et al 2008a;Starr et al 2012). It is well known that behavioral responses can be altered in complex ways because of the interaction between serotonergic and catecholaminergic systems.…”
Section: Changes In Eeg Activity In Serotonin Syndromementioning
confidence: 99%
“…This hypothesis can well explain the influences of underlying environmental factors for intensifying the MDMA-induced syndrome. It is known that MDMA can elicit an increase in many kinds of neurotransmitters in the brain (Nair and Gudelsky, 2006; Baumann et al, 2008; Starr et al, 2012; Anneken et al, 2013). In the absence of environmental factors, however, the responses of other kinds of neurotransmitters to MDMA are too small to have an impact on the syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate affinity (10µM-100µM) targets included the norepinephrine and dopamine transporters, and 5-HT 1 receptors, and low affinity (>100µM) targets included dopamine-D1 and -D2 receptors and the choline transporter. A small number of studies have shown that MDMA produces modest increases in extracellular levels of glutamate (Anneken & Gudelsky, 2012;Nash & Yamamoto, 1992) and acetylcholine (Acquas et al, 2001;Nair & Gudelsky, 2006a, 2006b), but there is limited evidence for effects on extracellular norepinephrine (Starr, Page, & Waterhouse, 2012) or GABA (Bankson & Yamamoto, 2004;Yamamoto, Nash, & Gudelsky, 1995). In contrast, a great deal of research on MDMA has focused on 5-HT and dopamine mechanisms.…”
Section: Pharmacodynamics Of Mdmamentioning
confidence: 99%